The association between mental demands at the workplace and cognitive functioning: the role of the big five personality traits. - Hussenoeder, F. S.; Conrad, I.; Roehr, S.; Glaesmer, H.; Hinz, A.; Enzenbach, C.; Engel, C.; Witte, V.; Schroeter, M. L.; Loeffler, M.; Thiery, J.; Villringer, A.; et al. (Aging Ment Health, 2020)
Objectives: Mental demands at the workplace can be preventive against cognitive decline. However, personality shapes the way information is processed and we therefore assume that Neuroticism, Extraversion, Openness, Agreeableness and Conscientiousness, would moderate the beneficial effects of workplace stimulation on cognitive outcomes.Methods: We analyzed data from the population-based LIFE-Adult-Study (n = 6529). Cognitive outcomes were assessed via the Trail-Making Test (TMTA, TMTB) and the Verbal Fluency Test. Personality was assessed via the Personality Adjective List (16 AM). Mental demands were classified with the indices Verbal and Executive based on the O*NET database.Results: Multivariate regression analyses showed only two significant moderation effects of personality, i.e. in individuals with low scores on Conscientiousness/Openness, index Verbal was connected to better TMTB performance, while this effect disappeared for individuals with high values on the personality trait. However, the additional explained variance remained marginal.Conclusion: The findings suggest that personality does not modify associations between high mental demands at work and better cognitive functioning in old age; however, there is a tendency that high levels of Openness and Conscientiousness may offset effects of mental demands.
Keywords: *Cognition; *Extraversion, Psychological; Humans; Neuroticism; Personality; *Workplace